A study on haemolytic disease - Rajakanthan, K.; De Mel, W.C.P.; Sheriff, M.H.R. (My University, 1991)
Patients with haemolytic disease treated in the General Hospital, Colombo during the period March to November, 21990 were studied. The pattern of haemolytic disease presenting to general medical wards was analysed. During this eight month period, 42 patients were treated, 24 (57%) were females and 18 (43%) were males. Their ages raged from 12 to 65 years. 63% being in the 20 to 40 year age of group. Mean age of the study group was 32yr. Analysis of presenting complaints revealed that 90% of patients had jaundice, 61% had shortness of breath of generalized weakness and fatigue. Analysis of the clinical signs revealed that the splenic dullness was increases in all patients. The spleen size varied from just palpable to 6 am from the left costal margin with a mean of 2.96 cm. The liver was palpable in 92% of patients with a mean size of 2.94 cm below the costal margin. Analysis of the haematological parameters revealed that the haemoglobin of these patients varied from 2.8 to 8.6g/dl with a mean of 5.79 g/dl. The reticulocyte count varied from 8% to 48% with mean of 17.35%. Five patients were seen with acute severe haemolysis. 17 patients (40%) had congenital haemolytic anemia of which 13 patients (31% of total) had thalassaemia. Four patients were found to be double heterozygote for HbE and HbS.(3Hb E-thal and one sickle thal). The other intracorpuscular defect observed was G6PD deficiency, found in 4 patients (9%). Of the acquired haemolytic anaemia 72% (18 pateints, 43% of total patients) had auto immune haemolytic anemia 60% being direct Coombs positive.